2015
DOI: 10.4155/bio.15.133
|View full text |Cite
|
Sign up to set email alerts
|

A New DBS Card with Spot Sizes Independent of The Hematocrit Value of Blood

Abstract: Quantitative measurements over a broad Ht range show nonbiased results compared with whole spot analysis. The cards are experienced as reproducible, robust and easy to use on aspects of punchability and extractability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Furthermore, Mengerink et al presented the use of a hydrophilically coated woven polyester fiber as a Hct-independent substrate for DBS analysis, named Qyntest cards (Qynion, Geelen, The Netherlands). It was demonstrated that the cards generate spots with a Hct-independent size within a Hct range of 20 to 70%, allowing to use partial spot analysis without the Hct volume bias [55]. A clear drawback here is that this is a completely distinct material, which also may be more expensive to produce, as compared to conventional cellulose-based cards.…”
Section: Minimizing the Hct Issuementioning
confidence: 99%
“…Furthermore, Mengerink et al presented the use of a hydrophilically coated woven polyester fiber as a Hct-independent substrate for DBS analysis, named Qyntest cards (Qynion, Geelen, The Netherlands). It was demonstrated that the cards generate spots with a Hct-independent size within a Hct range of 20 to 70%, allowing to use partial spot analysis without the Hct volume bias [55]. A clear drawback here is that this is a completely distinct material, which also may be more expensive to produce, as compared to conventional cellulose-based cards.…”
Section: Minimizing the Hct Issuementioning
confidence: 99%
“…The small volume decreases sensitivity and accuracy of quantitation, while non-uniform blood distribution across a DBS and changes in hematocrit levels can arise due to collection volume uncertainty. Non-homogeneity across a DBS sample have been addressed with a variety of approaches, including whole spot analysis and volumetric sampling 30 37 , 47 , 48 . We have developed a specially designed volumetric blood collection device which yields a sufficient quantity of sample to test any number of proteins in a multi-plex immunoassay, with bleeding capacity being the most significant limiting factor of sample volume.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Moreover, some types of collection devices have been reported to be less affected by the HT effect and may help to overcome this issue. 35,36 Additionally, chitosan and alginate foams have been proposed as collection substrates to help increase analyte recovery, as they dissolve during sample extraction. 37 Although most DBS-based bioanalytical methods use regular, cellulose-based, untreated filter paper (cards), for certain applications it may be valuable to evaluate the use of pretreated or non-cellulose-based alternatives.…”
Section: A C C E P T E Dmentioning
confidence: 99%